Resilience and the cash infrastructure: The role of access, acceptance, availability, and affordability - Gerhard Rösl; Franz Seitz (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2024)
We analyze the role of a well-functioning cash infrastructure for the stabilizing role of cash and the resilience of cash cycles. For that purpose, experiences from developed countries with low and high cash usage are assessed by distinguishing between demand and supply factors to demonstrate that cash has to keep a vital role as a means of payment not only to maintain its status of a highly liquid store-of-value but also as an efficient tool to combat crises. To do so, access, availability, acceptance, and affordability of cash are crucial building blocks of a robust cash infrastructure. Important aspects are also the public good characteristics of the "institution" cash which should encourage central banks to re-evaluate their position of "neutrality" as a player in the payments market to a more active role. – – Wir analysieren die Rolle einer gut funktionierenden Bargeldinfrastruktur für die stabilisierende Rolle von Bargeld und die Resilienz des Bargeldkreislaufs. Zu diesem Zweck werden Erfahrungen aus entwickelten Ländern mit geringer und hoher Bargeldnutzung ausgewertet und zwischen Nachfrage- und Angebotsfaktoren unterschieden. Es wird abgeleitet, dass Bargeld als Zahlungsmittel wichtig ist, damit es als hochliquides Wertaufbewahrungsmittel fungieren kann und als effizientes Instrument zur Krisenbekämpfung zur Verfügung steht. Dementsprechend sind Zugang, Verfügbarkeit, Akzeptanz und Erschwinglichkeit von Bargeld entscheidende Bausteine einer robusten Bargeldinfrastruktur. Wichtige Aspekte sind auch die Öffentliches-Gut-Eigenschaften der "Institution" Bargeld, die impliziert, dass Zentralbanken ihre "neutrale" Position als Akteur im Zahlungsverkehr überdenken sollten, um eine aktivere Rolle bei der Unterstützung von Bargeld einzunehmen.
Keywords: E41; E51; E58; O57; 330; Cash; banknotes; ATM; cash infrastructure